PRESERVICE ENGLISH TEACHERS' BELIEF IN EMPOWERMENT WITH FIVE DIMENSIONS IN THE TEACHING LANGUAGE EDUCATION PROGRAM - Maisa Rahman, - (2021)
ABSTRACT Recently, empowerment has been a critical component of transformative value, as higher education is an ongoing process of student transformation. Nevertheless, the conservative teaching practices often disempower students, affecting preservice teachers' learning-unlearn-relearn situation. This study investigates the preservice teachers' belief in the empowerment process and how the preservice teachers perceive the belief in English language teaching. It employed a qualitative case study design. Purposive sampling was used to gain the participants' belief in the holistic empowerment process at an English education program in Indonesia. The results indicate that preservice English teachers believe they could be more confident in knowledge dimension than other dimension, especially in technology knowledge. First, most preservice teachers perceive that their teacher knowledge is good, meanwhile the experiential knowledge is moderate. Second, some participants perceive that they have a good learning interest and habit, but they perceive a moderate level of motivation and commitment to learning. Third, most participants perceive that they have good competence, especially communication, critical thinking, collaboration, and creativity during the program. Fourth, most participants perceive that they have a life-changing experience associated with personal growth, such as self-awareness, self-efficacy, and self-direction. Fifth, most participants share similar concerns about technology limitations but attempt to connect to the learning community through online group discussion. Thus, most participants consider that the empowerment process is dynamic and multifaceted and cannot be limited to a single dimension and time, for it requires a lengthy iterative process across multiple elements.